New Techniques for the Detection of Nuclear and Radioactive Agents - Aycik, Gul Asiye; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2009)
Nuclear and radioactive agents are considerable concerns especially after the early 1990s and more attention has been focused on the radiation detection technologies. This book comprises the selected presentations of NATO Advanced Training Course held 26-30 May 2008 in Mugla, Turkey. The contributions represent a wide range of documents related to control, monitoring and measurement methods of nuclear / radioactive isotopes and agents for both fundamental and applied works dealing with their use for different purposes. This book presents environmental data from many locations of different countries and also contains the contributions in the detection/monitoring programs of some authors from CIS countries. The basic goal of this book is to deal with recent developments and applications of environmental monitoring and measurement techniques of environmental radionuclides and nuclear agents as well as the auxiliary techniques. The many recent examples contributed by authors will be useful in monitoring/ measurement studies of radioactive/nuclear agents in the present environment, and can help, not only in carrying out outdoor and laboratory experiments, but also in protection of possible sources of radionuclides and nuclear agents. Especially the contributions of experts and specialists involved in this book assured the highest level of knowledge in the field of techniques for the detection of radioactive and nuclear agents.
Overview Of The Radioactive And Nuclear Agents In The Environment -- The Localization Of Gamma Emitting Point Source In A Large Medium By Multi Detectors Measurement -- Environmental Radionuclides Measured By Ams -- Combination Of Radiochemical And Activation Techniques For The Detection Of Radionuclides -- The Concept Of Virtual Point Detector For Voluminous Gamma Detectors -- The Localization Of A Small Neutron Source In A Homogeneous Medium -- Passive Solid State Dosimeters In Environmental Monitoring -- The Challenges For Investigation/Detection In Combating Trafficking Of Radioactive Sources In Albania -- Macedonian Experience In Metal Scrap Monitoring At Border Crossings -- Radiation Monitoring At The Borders Of Republic Of Uzbekistan With The Use Of Portal Monitors -- The Ukrainian Experience Of Application Of Guarantees Of Non-Proliferation And Requirements Of The Additional Protocol -- Modern Condition Of Uranium Provinces In Kyrgyzstan (In Areas Of Kadji-Sai And Min-Kush) -- Instruments For Detecting The Unsanctioned Displacement Of Radioactive Materials -- Practical Instrumentation Considerations When Planning A Radiation Monitoring Program For The Field And The Laboratory -- Gamma Spectrometry In The Field -- Gas-Filled And Plastic Scintillation Detectors: Advantages And Disadvantages -- Efficiency Calibration Of A Well-Type Ge Detector For Voluminous Samples In Cylindrical Geometry -- Environmental Monitoring At Kfki Campus -- The Problem Of Vulnerable Ionizing Radiation Sources In Republic Of Moldova -- Measurement Of Naturally Occurring Radionuclides With Several Detectors: Advantages And Disadvantages -- Preparation Of Radionuclides And Their Measurement By High Resolution ?-Spectrometry, ?-Spectrometry And High Resolution ?-Spectrometry -- Determination Of Radionuclides In Environmentals Samples -- Radiological Investigation Of Issy-Kul Region Of Kyrgyz Republic -- Working Together For Nuclear Safety -- Environmental Studies in Uzbekistan Institute of Nuclear Physics With the Use of Nuclear Methods -- Radiobiological Effects Of 241 Am Incorporated In Cells Of Organism And Methods Of Prevention Of The Menace Of Combined Toxicity Of The Transuranium Elements -- Testing And Performance Evaluation Of Illicit Trafficking Radioactivity Detectors -- Determination Of Lead-210 And Polonium-210 In Marine Environment.
Keywords: Environment; Physical measurements; Measurement; Nuclear engineering; Radiation protection; Radiation -- Safety measures; Environmental sciences; Environment; Environmental Monitoring/Analysis.; Measurement Science and Instrumentation; Nuclear Engineering; Effects of Radiation/Radiation Protection; Environmental Physics; Electronic books